Elective Primary or Secondary Delayed Sternal Closure Improves Outcome in Severely Compromised Patients - Calafiore, Antonio M.; Sheikh, Azmat A.; Alfonso, Juan J.; Tantawi, Tarek; Maklouf, Belgeit; Shawki, Ahmed; Allam, Ahmed; Awadi, Mohammed O.; Osman, Ahmed A.; Habib, Aly M.; Di Mauro, Michele (The Thoracic and Cardiovascular Surgeon, 2018)
Background Delayed sternal closure (DSC) in patients with severely compromised preoperative hemodynamics can be helpful as the chest sometimes cannot be able to contain both lungs and heart. We report our experience to evaluate the midterm results of this strategy in an adult population.Materials and Methods From May 2009 till July 2015, 33 patients had DSC as first treatment of severe hemodynamic deterioration after cardiac surgery. Surgical procedures were valvular (9.27%) or coronary artery bypass grafting + others (24.73%). Stepwise logistic regression (SLR) showed that patients with lower ejection fraction, dilated right ventricle, and severe pulmonary hypertension were more likely to need DSC. Patients were divided in two groups: group A (n = 17), when the sternum was reopened before any hemodynamic collapse, or was never closed, and group B (n = 16), when the sternum was reopened after hemodynamic collapse.Results Inhospital mortality was 39% (n = 13), 18% in group A and 62% in group B (p < 0.0001). In 28 patients where the sternum was reopened, cardiac index increased from 1.7 (1.6, 1.9) L/m2 to 2.8 (2.4, 3) L/m2, p < 0.0001. The sternum was closed in 28 patients (85%), 94% in group A and 75% in group B (p = 0.13), after a median of 4 (2.5) days. SLR showed that only group B (p < 0.0001) was a risk factor for early death. Two-year survival was 48 ± 9%, higher in group A (71 ± 13) than in group B (25 ± 11), p < 0.0001. Cox's analysis showed that group B (p < 0.0001) and redo (p < 0.0001) were risk factors for lower survival.Conclusion Elective DSC represents a useful strategy in severely compromised patients, entailing an improvement of hemodynamics and a higher survival.
Keywords: cardiac failure; instruments; sutures; surgery; complications